Large Eddy Simulation of Bluff-Body Flame Approaching Blow-Off: A Sensitivity Study. Issue 10 (3rd October 2019) - Hodzic, Erdzan; Jangi, Mehdi; Szasz, Robert-Zoltan; Duwig, Christophe; Geron, Marco; Early, Juliana; Fuchs, Laszlo; Bai, Xue-Song
ABSTRACT: As almost all combustion processes of practical interest take place in the presence of turbulence, the development of the increasingly refined turbulence–chemistry interaction (TCI) models has led to highly sophisticated approaches. Nearly all of the studies comparing different models focus on stable premixed/non-premixed flame configurations. In this work, the focus is on well-documented, lean premixed bluff-body stabilized flames approaching blow-off and on the blow-off sequence itself. Large Eddy Simulations (LES) have been used to capture the time-dependent, three-dimensional flow-field using Transported Probability Density Function (TPDF), Partially Stirred Reactor Model (PaSR), and Implicit LES (ILES) models. Furthermore, the influence of finite-rate chemistry and different chemical mechanisms is evaluated to determine the limitation and capability of the different TCI approaches for modeling flames just prior to and during the transient blow-off process. While the average flow-fields do not reveal any significant differences between modeling approaches, detailed analysis of the flame reveals that there are differences in the predicted flame thickness and composition. The ability of the considered TCI models to predict local as well as full-flame extinction during the blow-off is investigated as well. It is demonstrated that such a blow-off sequence is not always governed by complex chemistry.